The effect of solid solution and gamma prime on the deformation modes in Ni-based superalloys. (1st August 2020) - Harte, Allan; Atkinson, Michael; Smith, Albert; Drouven, Carsten; Zaefferer, Stefan; Quinta da Fonseca, João; Preuss, Michael
Abstract: Understanding the deformation, strengthening and failure mechanisms in polycrystalline nickel-base superalloys is necessary to develop next generation alloys for application in highly demanding environments. Here, the aim is to examine the various ways in which solution- and γ' precipitation-strengthening affect the deformation behaviour of three Ni-based superalloys through deformation mapping and investigation at multiple length-scales. This is achieved using high-resolution digital image correlation to quantify local strain, electron backscattered diffraction for lattice rotations and electron channelling contrast imaging to investigate dislocation-mediated mechanisms of deformation. This approach bridges the gap between nano-scale microscopy of dislocation-γ' interactions and macro-scale measurements of mechanical properties, such as yield stress, flow stress and the strain-hardening rate. Deformation in solution-strengthened alloys progresses by a slip band refinement mechanism, which results in low levels of dislocation pileup at grain boundaries and so better grain deformation compatibility with neighbours. Deformation in the γ'-strengthened alloys evolves through a glide plane softening mechanism and the resulting high strain localisation impinges on grain boundaries, creating diffuse strain regions at the boundary. In the coarse-γ' variant there is more Orowan looping and cross slip around larger precipitates, more slip planes are active and more grain-scale cross slip takes place, resulting in greater local friction stresses and therefore greater macroscopic flow stresses and strain-hardening rates. We provide evidence of greater interaction between intersecting non co-planar slip bands in the γ'-strengthened alloys, which contributes to the strain-hardening by progressively decreasing the slip distance. This mechanism is not observed in the solution-strengthened alloy. Graphical abstract: Image, graphical abstract